Rethinking the Russo-Japanese war, 1904-05.
1 online resource.
Keywords: Despite the growing number of publications on the Russo-Japanese War, an abundance of questions and issues related to this topic remain unsolved, or call for a reexamination. This 30-chapter volume, the first in the two-volume project Rethinking the Russo-Japanese War, provides a comprehensive reexamination of the origins of the conflict, the various dimensions of the nineteen-month conflagration, the legacy of the war, and its place in the history of the twentieth century. Such an enterprise is not only timely but unique. It has benefited from a multinational team of thirty-two scholars from twelve nations representing a broad disciplinary background. The majority of them focus on topics never researched before and without exception provide a novel and critical view of the war. This reexamination is, of course, facilitated by a century-long perspective as well as an impressive assortment of primary and secondary sources, many of them unexplored and, in a number of cases, unavailable earlier.